2019
DOI: 10.31729/jnma.4631
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Alcoholic Liver Disease in a Tertiary Care Center: A Descriptive Cross-sectional Study

Abstract: Introduction: Alcoholic liver disease is a serious health problem related to an unhealthy lifestyle. The three most widely recognized forms of alcoholic liver disease are alcoholic fatty liver, acute alcoholic hepatitis, and alcoholic cirrhosis. The main aim of our study is to find out the prevalence of alcoholic liver disease in tertiary care center. Methods: A descriptive cross-sectional study was conducted among inpatient cases admitted in the medicine department of tertiary care center from 1st June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
(24 reference statements)
5
5
0
Order By: Relevance
“…With regards to the gender-wise distribution of the patients, our study showed that ALD was more predominant in males which is similar to other studies. 3 , 9 Similarly, our study reported that the mean serum values of serum bilirubin levels, AST and ALT were increased in the majority of the cases which held true in other studies as well which could indicate hepatocellular damage. 3 , 10 …”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…With regards to the gender-wise distribution of the patients, our study showed that ALD was more predominant in males which is similar to other studies. 3 , 9 Similarly, our study reported that the mean serum values of serum bilirubin levels, AST and ALT were increased in the majority of the cases which held true in other studies as well which could indicate hepatocellular damage. 3 , 10 …”
Section: Discussionsupporting
confidence: 85%
“… 3 , 9 Similarly, our study reported that the mean serum values of serum bilirubin levels, AST and ALT were increased in the majority of the cases which held true in other studies as well which could indicate hepatocellular damage. 3 , 10 …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…al [ 51 ] showed that hepatocarcinogenesis is a time-dependant progression of benign to malignant nodules and this was illustrated in our study, by the presence of regenerative nodules in younger patients with more HCC nodules observed in the older population. Rizal et al [ 52 ] demonstrated that cirrhosis, regardless of aetiology, is more prevalent in men, worldwide. This gender predilection was seen involving all three groups in our study, which was in line with these observations.…”
Section: Discussionmentioning
confidence: 99%